Break out! [compact disc, unabridged] : 5 keys to go beyond your barriers and live an extraordinary life - Osteen, Joel (Hachette Audio, 2013)
Osteen believes we were all created by God to make a difference in our generation. He says that the creator gave all people the chance at greatness, and that it's the ability to overcome hardships that can lead people to reach their potential. Osteen gives practical stages and support for making a life without boundaries. Will assist listeners to break free in order to trust bigger, increase productivity, enhance relationships and achieve dreams.